Stapled haemorrhoidectomy versus openhaemorrhoidectomy: a prospective comparative study - Bhandari, R S; Lakhey, P j; Singh, Y P; Mishra, P R; Singh, K P (Journal of Chitwan Medical College, 2015)
Open haemorrhoidectomy (OH) treatment has been reserved for prolapsing haemorrhoidal disease (third and fourth grade) and comprehends excision of haemorrhoidal tissue and is associated with significant postoperative pain. As an alternative approach, many randomized controlled trials have shown consistent advantage with haemorrhoidopexy (SH) in terms of postoperative pain, analgesic requirement, length of surgical procedure, short recovery time and early return to normal activities. This study has been conducted to compare the short-term outcome of SH with OH. A prospective comparative study, which included grade 3 and 4 haemorrhoids and comparing short Term outcomes between SH and OH was conducted in the Surgical Gastroenterology units of University Teaching Hospital. A total 44 patients, 22 in each group were compared. Age (SH 42±10.80 Vs. OH 45±13.30) and sex (SH, M:F-9:13 Vs. OH, M:F-14:8) distribution was comparable. Also, the groups were comparable in terms of symptom duration in years (SH, 3.20±2.26 Vs. OH, 2.31±2.47) and distribution of haemorrhoid grades. The SH group showed significant advantage in terms of postoperative pain (Average pain score SH, 2.73±1.20 Vs. OH, 5.20±1.91) and analgesic use (SH 2.32±0.94 Vs. OH 9.32±2.62). Similarly the operating time (time in minutes SH, 42±7.34 Vs. OH, 57.50±8.27), hospitals stay (days of stay SH, 2.90±0.68 Vs. OH, 3.77±0.86) and return to preoperative activity (days to return SH, 7.9±4.90 Vs. OH, 13.6±5.60) were also significantly shorter in the SH group than the OH group. The short-term complications were similar in both groups (P value >0.05). In conclusion, SH has better short-term outcome compared with OH and SH is a viable addition to the therapy options available for haemorrhoids. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11956